The Challenge of Providing “Legal Representation” in the United States, South Africa, and China - Charles J. Ogletree Jr. (Washington University Journal of Law & Policy, 2001)
This Article evaluates which of the models and methods employed in the United States could be effectively implemented in China and South Africa.
Keywords: Legal assistance to the poor – United States; Legal assistance to the poor – South Africa; Legal assistance to the poor; Right to counsel – United States; Right to counsel – South Africa; Right to counsel; Comparative law; Constitutional law; Equal protection